FOREIGNERS’ ACQUISITION OF IMMOVABLE PROPERTY IN THE FRAMEWORK OF LEGAL BASIS, SOCIOLOGICAL RISKS AND SUGGESTIONS - Dolunay, Ayhan; Kasap, Fevzi (Revista Gênero e Interdisciplinaridade, 2021)
Persons are not subject to citizenship or, in other words, states that they consider to be foreigners are subject to the rules / restrictions imposed on them by the state concerned if they wish to acquire immovable property in the territory of their sovereignty and where immovable acquisition of foreigners is possible in the country of the immovable. In our work, the issue of foreigners’ acquisition of foreigners in the North Cyprus, which is regarded as a national issue in terms of the Turkish world. The concepts of "foreign" and "immovable" shall be defined first and then by considering the rules / limitations on the immovable acquisition of foreigners in the North Cyprus, the method of acquisition in accordance with law and the method of acquisition which is frequently applied and the territories of the North Cyprus. Far beyond, the Turkish Cypriot people; we will propose solutions to overcome this serious issue and the other negativities that have been identified by evaluating the acquisition method by cheating against the blood which may lead to "assimilation" of the Turkish people in the island